Does the Numeric Rating Scale (NRS) represent the optimal tool for evaluating pain in the triage process of patients presenting to the ED? Results of a muticenter study - Capponi, Rebecca; Loguercio, Valentina; Guerrini, Stefania; Beltrami, Giampietro; Vesprini, Andrea; Giostra, Fabrizio (Acta Biomedica Atenei Parmensis, 2017)
Abstract: Pain evaluation at triage in Emergency Department (ED) is fundamental, as it influences significantly patients color code determination. Different scales have been proposed to quantify pain but they are not always reliable. This study aims to determine a) how important is for triage nurses pain measurement b) reliability of Numeric Rating Scale (NRS), the most used instrument to evaluate pain in Italian EDs, because it frequently shows higher pain scores than others scales. Methods: End point 1: a questionnaire was administered to triage nurses in some hospitals of northern Italy. End point 2: 250 patients arriving at the ED referring pain have been evaluated using, randomly, either the NRS or a fake “30-50” scale. Results: End point 1: Triage nurses acknowledge to modify frequently the referred pain intensity. This for several reasons: nurses think that patients may exaggerate to obtain a higher priority color code; they may be influenced by specific patients categories (non EU citizens, drugs-addicted, elderly); the pain score referred by patients is not correspondent to nurse perception. End point 2: Data show that the mean value obtained with NRS is significantly (p